Surgical preference regarding different materials for custom-made allograft cranioplasty in patients with calvarial defects: Results from an internal audit covering the last 20 years. (April 2020) - Ganau, Mario; Cebula, Helene; Fricia, Marco; Zaed, Ismail; Todeschi, Julien; Scibilia, Antonino; Gallinaro, Paolo; Coca, Andres; Chaussemy, Dominique; Ollivier, Irene; Ligarotti, Gianfranco K.I.; des Neiges Santin, Marie; et al.
Highlights: Cranioplasty (CP) restores cranial vault following decompressive craniectomy (DC). Studies provide only fragmentary information regarding the best timing and material for CP. We conducted an audit to identify local trends in choice of materials for CP. This study shows that PHA yields better outcomes than PMMA CP. Neurosurgeons should favor pragmatism and patient safety over costs. Abstract: Background: Secondary cranioplasty (CP) plays a key role in restoring cranial vault anatomy and normal brain function following decompressive craniectomy (DC). The scientific literature provides only fragmentary information regarding the best timing and material for CP, making a direct comparison of different materials difficult. Object: To identify and report according to STROBE guidelines local trends in choice of materials for CP, complications rate and surgical outcomes. Methods: We conducted an audit on secondary CP covering the last 20 years of surgical practice at our Institution. Custom-made CP used over the years were made of: porous hydroxyapatite (PHA), polymetylmethacrylate (PMMA), polyetheretherketone (PEEK), acrylic and titanium. The primary endpoint of this study was the incidence of postoperative complications, such as: implant infection, fracture and dislocation. Secondary endpoints were the followings: patients satisfaction with cosmetic result, rate of implant integration, and long-term neurological outcome. Results: A total of 218 patients were included, given the predominance of PHA (Group A) or PMMA (Group B) CP, a direct comparison was made only between those two groups. Overall reoperation rate was 6.5% versus 28%; implants' osseointegration rate was of 69% versus 24%; satisfaction rate was 66% versus 44%, in Group A and B respectively. Conclusions: This single-centre study provides Level 3 evidence that PHA yields better outcomes than PMMA CP. Designing a management algorithm for planning and executing CP is difficult for clinical and organizational reasons; till a widespread consensus is reached, neurosurgeons with subspecialty interest in neurotrauma should favor pragmatism and patient safety over costs.